Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Perbankan Syariah Di Indonesia - Nurdina Sureta; Kamaludin Kamaludin; Paulus Sulluk Kananlua (Student Journal of Business and Management, 2021)
The objectives of this research is to test the effect of Intellectual Capital components on the financial performance of Syariah banking, to verify the Intellectual Capital component with the most significant effect on the financial performance of Syariah banking, and also to verify the role of the average growth of Intellectual Capital in the financial performance of Syariah banking in Indonesia. The population of this study were all of Syariah public banking (BUS) which were listed in BEI from 2014-2018. The type of research used in this study was applied research. The sampling type employed was purposive sampling. Through purposive sampling, 10 banking companies were taken as samples with a total of 50 research observations. This study found that Intellectual Capital components did not at all have positive effects on both the financial performance and the increase of financial performance of Syariah banking in the present and future, and the average growth of Intellectual Capital will not all affect the financial performance of Syariah banking in the future.